Evaluasi Kebijakan Peningkatan Kualitas ASN Pemerintahan Provinsi Banten Dalam Meningkatkan Pelayanan Publik - rawinarno, tjahyo (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2019)
The Government of Banten Province in 2017 has a yellow public service compliance value for the assessment conducted routinely by the Indonesian Ombudsman Institute. This condition is interesting to study related to improving the quality of state civil apparatus, because the quality of state civil apparatus is correlation to the performance of public services. On the basis of research conducted illustrated Banten Provincial Government has a strong commitment in improving the quality of state civil apparatus as an effort to improve the quality of public services, although there are still some things that need to be improved. Commitment to improvement is illustrated by the intensity and quality of the training carried out, work control as an effort to realize work discipline and foster role models of superiors to subordinates. With the better quality of state civil apparatus owned by itself the quality of public services will increase significantly. It is not surprising when in 2018, the Indonesian Ombudsman gave an 80.74 compliance value from 50 administrative service products in Banten Province. This means that the public services of the Banten provincial administration are deemed appropriate to enter the green zone, parallel to the Provinces of West Java and DKI Jakarta.